Application of cleaner technology and experimental design for the reduction of chemical substance consumption in the hard disk drive arm coil assembly process - Premchai Moolla (2018)
The objective of this research is to apply the Cleaner Technology (CT) and Design of Experiment (DOE) concepts in the hard disk drive arm coil assembly process, in order to reduce chemical substance (i.e. epoxy and Isopropyl Alcohol (IPA)) consumption. In the production process, epoxy is used to fix the arms and coils, whereas IPA is used to clean the arms before they are delivered to the production process. These chemicals are toxic and cause irritation to workers if they are not careful. Furthermore, the ineffective use of these chemicals adversely affects production costs. The research methodology was divided into two main parts. The first part employed the CT concept to analyze the loss during production, as well as the causes of loss. Opportunities to reduce those losses could then be recommended. The next step was to further analyze and evaluate a particular CT opportunity using DOE. In this second part of the research, DOE was used to reduce the chemicals used in the process by finding the optimum amount of chemicals used which does not affect the quality of the product. Full factorial experiment 2k, with two replicates was used for screening the four factors, these being: IPA, work-piece curing, epoxy usage and air pressure. The response variable was the arm coil bonding force. The analysis of variance (ANOVA) was conducted. The results of the study show that the optimal operating conditions are: 1) to clean the arms without using IPA, 2) to cure the work-pieces, 3) the filling of 65 mg of epoxy between the arm and the coil, and that 4) there is no significant impact of the air pressure on the arm coil bonding force. The results of the confirmation test show that the arm coil bonding force is in accordance with customer specifications. The results of the experiment have subsequently been put into practice. Thus, reducing the amount of epoxy wasted in the production process helps save approximately 70,208 Baht per annum, while cleaning without using IPA can save 2,154,240 Baht per annum. In conclusion, applying CT and DOE can help to make overall cost savings of 2,224,448 Baht per annum.